Kualitas Kompos dari Berbagai Kombinasi Bahan Baku Limbah Organik - KUSMIYARTI, TATI BUDI (Agrotrop : Journal on Agriculture Science, 2015)
The Quality of Compost on Various Combinations of Organic Waste Raw Materials Evaluation of compost stability prior to its use is essential for the recycling of organic waste in agricultural soils. During composting, most of the biodegradable organic compound are broken down and a portion of the remaining organic material is converted into humic-like substances, with production of a chemically stabilized composted material. This experiment aimed to monitor the changes in physicochemical characteristics during composting of three kinds compost heap and to define parameters suitable for evaluating the stability of compost. The experiment were conducted from Mei to October 2011 and consisted of three treatments with six replicates for each treatment. Compost pile temperature,the pH, that reflected the initiation and stabilization of the compost, were measured during the composting process. The carbon organic material content, carbon and nitrogen content, the carbon to nitrogen ratio, organoleptic characteristics, and K2O, P2O5, Mg, Ca content were measured to evaluate the quality of the physicochemical properties of the compost. Compost toxicity level had evaluated using Germination Index. The result showed that the quality of compost from all treatments that were evaluated in this experiment meet the standard quality of SNI 2004.
Keywords: composting; compost stability; physicochemical characteristics.